Small-scale irrigation: opportunities for success - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Governments and international aid organizations have often seen the introduction of irrigation as a solution to the problems of low agricultural productivity, particularly in Africa. However, large-scale irrigation schemes have generally I proved...